Stimulation of endorphin massage, oxytocin massage, and suggestive (SPEOS) method activates let-down reflex (LDR) of postpartum mother - Ni Wayan Armini; Gusti Ayu Marhaeni; I Gusti Ayu Surati; Ni Made Dwi Malahayati; Ni Wayan Suarniti; Ni Komang Erny Astiti; Ni Luh Putu Sri Erawati (Poltekkes Kemenkes Yogyakarta, 2021)
Breast milk is the most important food, especially in the first months of a baby's life. The process of releasing milk also depends on the Let Down Reflex (LDR). One way to facilitate breast milk production is to apply the Stimulation of Endorphin Massage Oxytocin Massage, and Suggestive (SPEOS) method. The purpose of this study was to determine the effect of the SPEOS Method on LDR Activation Postpartum. The study design used a pre-experimental one-group pretest-posttest. The location of the study was conducted at the public health of Denpasar. The research period was from May to October 2019. The population was postpartum mothers at the public health care of Denpasar and fulfilled the specified inclusion criteria. The data collection instrument used a questionnaire. Statistical analysis with Wilcoxon test. The result found that the median of LDR postpartum before the SPEOS method (2 with a range of 1-3) and after the SPEOS method (5 with a range of 4-6) indicated an increase in the LDR score (p-value <0.001). SPEOS method increases the activation of LDR in postpartum. Public health centers and health workers need to compile and set operational standards for SPEOS procedures and implement this method for postpartum mothers.